Grandma Moses: Favorite Painter - Graves, Charles Parlin, 1911-1972.; Mays, Victor, 1927- (Champaign, Ill.: Garrard Pub. Co., 1969)
A biography of the New England grandmother who began painting seriously at age seventy and kept it up until she was over a hundred years old.
Keywords: Moses, -- Grandma, -- 1860-1961 -- Juvenile literature; Moses, -- Grandma, -- 1860-1961